Reprogramming of Mouse Calvarial Osteoblasts into Induced Pluripotent Stem Cells. (12th March 2018) - Wang, Yinxiang; Liu, Jessica Aijia; Leung, Keith K. H.; Sham, Mai Har; Chan, Danny; Cheah, Kathryn S. E.; Cheung, Martin
Abstract : Previous studies have demonstrated the ability of reprogramming endochondral bone into induced pluripotent stem (iPS) cells, but whether similar phenomenon occurs in intramembranous bone remains to be determined. Here we adopted fluorescence-activated cell sorting-based strategy to isolate homogenous population of intramembranous calvarial osteoblasts from newborn transgenic mice carrying both Osx1-GFP::Cre and Oct4-EGFP transgenes. Following retroviral transduction of Yamanaka factors (Oct4, Sox2, Klf4, and c-Myc), enriched population of osteoblasts underwent silencing of Osx1-GFP::Cre expression at early stage of reprogramming followed by late activation of Oct4-EGFP expression in the resulting iPS cells. These osteoblast-derived iPS cells exhibited gene expression profiles akin to embryonic stem cells and were pluripotent as demonstrated by their ability to form teratomas comprising tissues from all germ layers and also contribute to tail tissue in chimera embryos. These data demonstrate that iPS cells can be generated from intramembranous osteoblasts.